2019
DOI: 10.1111/dme.13911
|View full text |Cite
|
Sign up to set email alerts
|

How tightly controlled do fluctuations in blood glucose levels need to be to reduce the risk of developing complications in people with Type 1 diabetes?

Abstract: In 2011, the James Lind Alliance published a ‘top 10’ list of priorities for Type 1 diabetes research based on a structured consultation process. Whether reducing fluctuations in blood glucose can prevent long‐term microvascular and macrovascular complications was one of these. In this narrative review, 8 years on, we have assessed the updated evidence for the assertion that increased glucose variability plays an independent and clinically important role in the complications of Type 1 diabetes, over and above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…A case-control study confirmed the strong association ( r = 0.86) between MAGE and 8-iso-PGF2α urinary excretion rates ( 75 ), while another showed that transient hyperglycemia can induce lasting epigenetic changes in the promotor region of NFκB (a proinflammatory gene) in vitro and in mice ( 73 ). It is also established that high glycemia variability is associated with more frequent episodes of hypoglycemia, which contributes to a range of adverse effects including cardiovascular morbidity and mortality ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study confirmed the strong association ( r = 0.86) between MAGE and 8-iso-PGF2α urinary excretion rates ( 75 ), while another showed that transient hyperglycemia can induce lasting epigenetic changes in the promotor region of NFκB (a proinflammatory gene) in vitro and in mice ( 73 ). It is also established that high glycemia variability is associated with more frequent episodes of hypoglycemia, which contributes to a range of adverse effects including cardiovascular morbidity and mortality ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…A narrative review by Livingstone et al ( 76 ) explored the glucose variability hypothesis—the notion that glucose variability contributes additional risk of diabetes complications after adjusting for HbA 1c . While they agreed mechanisms for glycemic variability causing complications exist, they concluded that there were insufficient data at the time to substantiate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling blood glucose levels after a diagnosis of T1D is a constant challenge, with continuous lifetime risk of both severe hypoglycaemia and severe hyperglycaemia with ketoacidosis [2]. In the long-term, people with T1D are at increased risk of micro- and macrovascular complications due to lifetime exposure to imperfect glucose control [3,4]. The American Diabetes Association (ADA) treatment guidelines suggest a target HbA1c of <7.0% (53 mmol/mol) in adults with T1D (7.5% for youth with T1D) to reduce the risk of long-term diabetes-related complications [5].…”
Section: Introductionmentioning
confidence: 99%
“…2 It is generally agreed that reducing glucose excursion after meal improves overall glycaemic control, 3 although recent reviews have cast a doubt on the effect of short glucose variability on long-term diabetes complications. 4 Glucagon levels are physiologically suppressed at high plasma glucose concentrations. In the absence of diabetes and in T2D, glucagon level is found to be higher after oral glucose compared with isoglycaemic intravenous glucose infusion, although more insulin is secreted when glucose is administered by the oral route.…”
Section: Introductionmentioning
confidence: 99%